Peran Kepuasan Kerja Dan Komitmen Organisasi Dalam Memediasi Pengaruh Employee Engagement Terhadap Intention To Stay Guru Gen Z SD/MI di Kecamatan Srono - Ahmad Fauzi; Yuniorita Indah Handayani; Lia Rachmawati (Program Studi Manajemen Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2025)
Generation Z was often known as a dynamic generation that easily switched jobs. However, a different phenomenon was observed among Gen Z teachers in SD/MI in the Srono District, who showed a strong desire to remain in their profession. This study explored the factors that encouraged such loyalty, focusing on the role of employee engagement and how job satisfaction and organizational commitment served as bridges that strengthened their intention to stay. A quantitative approach was employed through questionnaire distribution and data analysis using the Structural Equation Modelling (SEM-PLS) technique. The results indicated that teachers’ involvement in their work (employee engagement) had a positive and significant influence on their intention to stay, both directly and indirectly through organizational commitment. Meanwhile, the indirect effect through job satisfaction was found to be insignificant. These findings conveyed an important message: when teachers felt valued, involved, and supported by their work environment, they developed into educators who not only stayed but also committed themselves to continuously serve and grow with their institutions.